Progress Report on the Activities of the Independent Evaluation Office. (Policy Papers; Policy Paper ;, 2007)
Since its April 2007 Report to the IMFC, the IEO has released its report on The IMF's Advice on Exchange Rate Policy, continued work on three other evaluations, and issued its Annual Report for 2006-07.